An MRI atlas of mouse basal ganglia - Ullmann, J.; Watson, Charles; Janke, A.; Kurniawan, N.; Paxinos, G.; Reutens, D. (Springer, 2013)
The basal ganglia are a group of subpallial nuclei that play an important role in motor, emotional, and cognitive functions. Morphological changes and disrupted afferent/efferent connections in the basal ganglia have been associated with a variety of neurological disorders including psychiatric and movement disorders. While high-resolution magnetic resonance imaging has been used to characterize changes in brain structure in mouse models of these disorders, no systematic method for segmentation of the C57BL/6 J mouse basal ganglia exists. In this study we have used high-resolution MR images of ex vivo C57BL/6 J mouse brain to create a detailed protocol for segmenting the basal ganglia. We created a three-dimensional minimum deformation atlas, which includes the segmentation of 35 striatal, pallidal, and basal ganglia-related structures. In addition, we provide mean volumes, mean T2 contrast intensities and mean FA and ADC values for each structure. This MR atlas is available for download, and enables researchers to perform automated segmentation in genetic models of basal ganglia disorders.